The Indian National Congress : centenary hindsights - Low, D. A. (Donald Anthony), 1927-2015. (Delhi ; New York : Oxford University Press, 1988)
Comprises seminar papers.
Includes bibliographies.
Keywords: Indian National Congress -- History; India -- Politics and government -- 1857-1919.; India -- Politics and government -- 20th century